2021
DOI: 10.1016/j.jairtraman.2021.102141
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of the COVID-19 pandemic on US airline stock prices

Abstract: This paper uses data at the trading day frequency and the method of local projections to quantify the dynamic responses of U.S. airline stock prices to a COVID-19 shock. We show that airline stock prices decline immediately by 0.1 percentage point in response to a 1% COVID-19 shock. In addition, the effect of the shock persists beyond the day on which it occurs, with most airline stock prices falling by as much as 0.6 percentage points after fifteen days. This negative response of airline stock prices to a COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
(40 reference statements)
0
17
0
2
Order By: Relevance
“…In addition, some studies explored the impact of COVID-19 on stock price reactions only in specific developed markets, such as the US ( Atems and Yimga, 2021 , Chen et al, 2022 ; Gavals et al, 2021; Kamal et al, 2021 ) or Europe ( Kökény et al, 2022 ). Although emerging economies contribute approximately 42% of the world’s gross domestic product ( Cavusgil et al, 2021 ), we still lack understanding regarding the extent to which COVID-19-related news affects transportation firm performance in emerging markets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some studies explored the impact of COVID-19 on stock price reactions only in specific developed markets, such as the US ( Atems and Yimga, 2021 , Chen et al, 2022 ; Gavals et al, 2021; Kamal et al, 2021 ) or Europe ( Kökény et al, 2022 ). Although emerging economies contribute approximately 42% of the world’s gross domestic product ( Cavusgil et al, 2021 ), we still lack understanding regarding the extent to which COVID-19-related news affects transportation firm performance in emerging markets.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers demonstrate the effect of COVID-19 pandemic on stock prices. For example, Ramelli and Wagner, 2020 , Atems and Yimga, 2021 , Ding et al, 2021 , Kamal et al, 2021 , Marobhe and Salaam, 2021 , Chan et al, 2022 , Martins and Cro, 2022 , and Sakawa and Watanabel (2023) investigate stock market reactions in the time of COVID-19 pandemic shock. In addition, we were motivated to fill the research gap Gong (2009) identified in calling for more transportation research that applies the event study approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related work analyzes the social and emotional perspectives of airline passengers [9] including their willingness to fly [10] and travel behaviors in pandemic times [11]. Broader issues concern long-term planning [12] and other strategic responses of the airlines to the pandemic [13,14], the governments' willingness to support airlines [15], the impact of the pandemic on transport markets [16], on airline industry [17] and on airline stock prices [18], the prospects for global recovery [19][20][21][22], and even the reconsideration of the entire foundation of the global aviation system [23]. Sun et al [24] provide a comprehensive review related to air transportation during the COVID-19 pandemic, while Riquelme et al [25] discuss the contagion modeling and simulation in transport and air travel networks in the context of COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The equity market is a seen as crucial as a driver of the economic sustainability of any country, including Indonesia (Bathia et al, 2020;Han & Tang, 2020;Lusiana, 2020a;Usman et al, 2021). Stock prices are a crucial reference before investing in the capital market (Atems & Yimga, 2021;Huang & Liu, 2021;Tao et al, 2022). Investors anticipate that the stock price will remain constant and will sometimes move upwards (Chin & Paphakin, 2021;Hogenboom et al, 2021;Ji et al, 2021;Tang & Yao, 2018).…”
Section: Introductionmentioning
confidence: 99%